Charactrization of follicular dynamicss and luteal function during short estrous cycle in suckled postpartum Mehsana buffaloes - AWASTHl, M K; KAVANI, F S; KAVANI, F S; SIDDIQUEE, G M; DHAMI, A J; PANCHAL, M T (The Indian Journal of Animal Reproduction, 2023)
The present study :Was aimed to characterize the pattern of follicular growth and progesterone concentratiodduring. short estrous cycle in postpartum suckled water buffaloes. Twenty freshly calved Mehsana buffaloctwere selected and. animals (n=3) showing short estrous cycle were scanned daily for ovarian follicular development.from day of first postpartum estrus to next using a real-time B-mode ultrasound scanner equipped with a 6.5MHz convex linear array transducer. The blood samples were collected from each animal on Days 3, 7 and IOafter first postpartum estrus for estimation of plasma levels of progesterone. These animals showed one-wavefollicular growth during short estrous cycle and short luteal phase with mean plasma progesterone concentratiodof0.49, 0.80 and 0.26 ng/ml on Days 3, 7 and i o· post-estrus, respectively, suggesting subnormal functioning of, CL. It is concluded that short estrous cycle is characterized by one-wave. of follicular development observed infew animals during early postpartum period in suckled water buffaloes.
Keywords: Follicular dynamics; Postpartum buffaloes; Short estrous cycle; Short luteal phase; Ultrasonography